The quality enhancement system improvement using the ANFIS method for segmentation of lecturer performance - Mutmainah, Mutmainah; Marfuah, Umi; Panudju, Andreas Tri (Jurnal Ekonomi Modernisasi, 2023)
Lecturers play a crucial role in developing skilled human resources. Classifying lecturer performance is believed to enhance the internal quality assurance system in the learning process and boost the scientific transformation process for students. This research aims to assess the effectiveness of using ANFIS as a classification approach for evaluating a lecturer's teaching ability. The study utilized a quantitative research method to evaluate the teaching performance of lecturers and a qualitative research method to analyze the internal quality assurance system at Universitas Muhammadiyah Jakarta. This study intends to use ANFIS to analyze instructor performance and pinpoint opportunities for enhancement in the college's internal quality assurance system. The study's findings suggest that ANFIS is an appropriate method for categorizing lecturers' performance, with an accuracy rate of 0.5. The insights can help pinpoint areas for development and guide actions to enhance the quality of education offered by the college. The study highlights the importance of using sophisticated approaches such as ANFIS to achieve continuous improvement and quality assurance in higher education institutions.